Rekonsiliasi Laporan Realisasi Anggaran Pendapatan dan Belanja Daerah (APBD) di Kabupaten Deli Serdang - Laiyinna Misqha Efendi; Rafika Ananda Putri; Zuhrinal M. Nawawi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to reconcile the Deli Serdang Regency Regional Revenue and Expenditure Budget Realization Report (APBD). This research uses descriptive research methods and a qualitative approach, examining the potential for solving contemporary problems using data collection, categorization and analysis methodologies. A qualitative approach to describe ongoing phenomena or determine the characteristics of data in the research period, with the aim of answering the main research questions. The results of the research, namely those affecting the APBN for the 2019–2022 Fiscal Year, show that the Deli Serdang Regency Government shows inefficiency in managing state revenues as evidenced by an efficiency ratio of only 80.86 percent. Deli Serdang Regency experienced a significant increase in revenue in the 2019–2022 budget year, in line with the regional government's success in maintaining or exceeding the revenue target from the previous budget year.